Urgensi Legalisasi Penggunaan Ganja Medis Dilihat dari Perspektif Hukum Hak Asasi Manusia - Riska Andini Hasnabila; Rasji (Syntax Literate, 2023)
Planning to legalize the use of marijuana for medical purposes in Indonesia has been discussed in the discussion of a draft law on changes to narcotics laws by Indonesian legislators. Testing of this narcotics law is one way that has been attempted in legalizing the use of marijuana for medical purposes. Viewed from a human rights perspective, every individual has the right to life and the right to health. This understanding certainly develops in the logic of society regarding the prohibition of the use of marijuana for medical purposes which is considered the same as prohibiting sick people from staying alive. This means that the state has failed to guarantee the lives of its citizens. However, on the other hand, some countries have legalized medical marijuana, such as Thailand, the United States, the Netherlands, Lebanon, Australia, and also Lebanon. While in Indonesia itself still prohibits the use of marijuana for medical purposes. With this research, it will be studied to find legal reasons from the government in the case of medical marijuana in Indonesia. These problems will then be analyzed using analytical descriptive methods to find new concepts related to the legalization of medical marijuana in Indonesia. The study suggests that medical marijuana will likely have legal potential in the future. This urgency is also demonstrated by the political will of the Indonesian Ulema Council and the Ministry of Health. From this research, it is hoped that it will provide recommendations related to proper educational insights about medical marijuana and the potential for legalization in the future.